Coupling research on employment centers and their service area with rail transit network-a case study of Shanghai, China - Wang Jun-Li; Hu Gang-Yu; Huang Jian-Zhong; Zhang Tian-Ran; Wang Jing-Xin (Frontiers of Urban and Rural Planning)
Abstract The coordination between urban space and transportation system facilitates the healthy development of urban spatial structure. The coupling of employment centers with the rail transit network is significantly important for optimizing urban spatial structure, developing employment centers and ensuring the efficient operation of rail transit. The urban rail transit network represents a typical complex network system, where calculating centrality and other indicators based on its spatial topology is crucial for analyzing of network and node characteristics. Using Baidu LBS data and rail transit network data in Shanghai as a case study, this paper examines the distribution, level and service area of urban employment centers. It assesses these factors based on employment density and commuting connection intensity, identifying hinterlands and spheres of influence. Additionally, the paper constructs the topological network of the rail transit system and calculates its topological indices. It analyzes the external spatial coupling patterns and internal interaction mechanisms among employment centers, their service areas, and the rail transit network. This analysis provides recommendations for optimizing Shanghai's spatial structure and rail transit system. Key findings include: 1) The method based on employment density effectively identifies major employment centers in Shanghai's central urban areas. 2) Employment centers are predominantly concentrated in Shanghai's central urban areas, forming multiple employment cores, with indications of a developing "dual core" trend along both sides of the Huangpu River. Various types of employment centers exhibit distinct hinterlands and spheres of influence based on location, industry, and land use functions. Compared to other centers, regional center has a strong distribution of sphere of influence of employment centers. 3) The number and accessibility of rail transit stations significantly influence the ability to gather large numbers of employees, supporting the radial expansion of employment centers. Intermediary hub stations are crucial for managing passenger flows between suburbs and the city center.4) Shanghai needs to enhance the construction of multi-modal rail transit network, improve construction standards, and integrate suburban employment centers with local influence zones to develop a multi-level rail transit network that provides essential support for suburban employment centers.